Instrument Evaluasi Non-Tes Ranah Afektif dan Psikomotorik Pembelajaran IPA Sinkronisasi Berbasis Keterampilan Abad 21 Di SMP Negeri 6 Sungai Penuh - Sri Anika Cahayu; Ratu Sampurna; Nadira; Risnita (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, 2023)
Education in 21st centuries is a technology-based learning that demands the creation of quality students in developing abilities in various skills. 21st century skills are divided into four categories including Ways ofthinking, Ways of working, Tools for working, Skills for living. Science is a discipline that has characteristics of scientific attitudes and practicums to achieve learning effectively and efficiency. The use of assessment in learning activities is a tool to see the development of students' skill abilities. This, of course, pays special attention to non-test evaluation instruments that are neglected in the affective and psychomotor assessment in science learning. The purpose of this study is to see the picture of science teachers in using non-test evaluation in the assessment of learning outcomes in the affective and psychomotor realms based on 21st century skills.The research method used is descriptive qualitative with observation techniques for data collection through questionnaires. The results showed that science teachers at SMP Negeri 6 Sungai Penuh were still low in using non-test evaluation instruments. The indicators showed that teachers have difficulty using non-test evaluation instruments, did not have time to prepare non-test evaluation instruments in the affective and psychomotor domains, and the conceptual assessment paradigm of the cognitive realm that is dominant in testing the abilities of learners in science learning activities.